68Ga-P15-041, A Novel Bone Imaging Agent for Diagnosis of Bone Metastases - Guo, Rui; Meng, Xiangxi; Wang, Fei; Yu, Jiangyuan; Xie, Qing; Zhao, Wei; Zhu, Lin; Kung, Hank F.; Yang, Zhi; Li, Nan (Frontiers in Oncology, 2021)
Objectives 68Ga-P15-041 (68Ga-HBED-CC-BP) is a novel bone-seeking PET radiotracer, which can be readily prepared by using a simple kit formulation and an in-house 68Ga/68Ge generator. The aim of this study is to assess the potential human application of 68Ga-P15-041 for clinical PET/CT imaging and to compare its efficacy to detect bone metastases of different cancers with 99mTc-MDP whole-body bone scintigraphy (WBBS). Methods Initial kinetic study using Patlak analysis and parametric maps were performed in 5 histopathologically proven cancer patients (3 male, 2 female) using 68Ga-P15-041 PET/CT scan only. Another group of 51 histopathologically proven cancer patients (22 male, 29 female) underwent both 99mTc-MDP WBBS and 68Ga-P15-041 PET/CT scans within a week, sequentially. Using either pathology examination or follow-up CT or MRI scans as the gold standard, the diagnostic efficacy and receiver operating characteristic curve (ROC) of the two methods in identifying bone metastases were compared (p <0.05, statistically significant). Results Fifty-one patients were imaged, and 174 bone metastatic sites were identified. 68Ga-P15-041 PET/CT and 99mTc-MDP WBBS detected 162 and 81 metastases, respectively. Sensitivity, specificity, positive predictive value, negative predictive value and accuracy of 68Ga-P15-041 PET/CT and 99mTc-MDP WBBS were 93.1 % vs 81.8%, 89.8 % vs 90.7%, 77.5 % vs 69.2%, 97.2 % vs 93.4% and 90.7% vs 88.4%, respectively. Our results showed that the mean of SUVmax was significantly higher in metastases than that in benign lesions, 15.1±6.9 vs. 5.6±1.3(P < 0.001). Using SUVmax = 7.6 as the cut-off value by PET/CT, it was possible to predict the occurrence of metastases (AUC = 0.976; P < 0.001; 95% CI :0.946-0.999). However, it was impossible to distinguish osteoblastic bone metastases from osteolytic bone lesions. Parametric maps based on Patlak analysis provided excellent images and highly valuable quantitative information. Conclusions 68Ga-P15-041 PET/CT, offering a rapid bone scan and high contrast images in minutes, is superior to the current method of choice in detecting bone metastases. It is reasonable to suggest that 68Ga-P15-041 PET/CT could become a valuable routine nuclear medicine procedure in providing excellent images for detecting bone metastases in cancer patients.